2010
DOI: 10.1007/s10502-010-9116-z
|View full text |Cite
|
Sign up to set email alerts
|

Only with your permission: how rights holders respond (or don’t respond) to requests to display archival materials online

Abstract: The study found that significant time is required to contact and negotiate with rights holders and that the biggest obstacle to getting permission is non-response. Of those requests that get a response, the vast majority are to grant permission. While few of the requests were met with denial, the data suggest that commercial copyright holders are much more likely to deny permission than other types of copyright holders. The data also show that adherence to the common policy of only displaying online those docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…The literature suggests that many of the general innovation challenges are challenges also when digitizing cultural heritage. They include, for example, lack of resources [9][10][11], insufficient training [10,12], technology [13], and organizational culture [14,15]. Innovation and digitalization have long been seen as being essential for organizational competitiveness and success [16,17].…”
Section: Background and Related Research On Museums And Ismentioning
confidence: 99%
“…The literature suggests that many of the general innovation challenges are challenges also when digitizing cultural heritage. They include, for example, lack of resources [9][10][11], insufficient training [10,12], technology [13], and organizational culture [14,15]. Innovation and digitalization have long been seen as being essential for organizational competitiveness and success [16,17].…”
Section: Background and Related Research On Museums And Ismentioning
confidence: 99%
“…In separate case studies, Dharma Akmon and Maggie Dickson found that the efforts required to identify and locate rights holders to obtain permission to digitize and display individual items far outweighed the permissions actually obtained. 8 A European study of the costs of rights clearance for digitization found that "the cost of clearing rights may amount to several times the cost of digitising the material." 9 However, Katie Fortney's case study of the copyright issues involved in creating the Grateful Dead Archives Online website reported different approaches to copyright, depending on the type of material.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Akmon reports that the biggest obstacle to getting permission is nonresponse to requests. 53 Archives have traditionally considered nonresponse the same as refusal to grant permission, and Akmon suggests that archives may want to reconsider this extremely risk-averse stance, as it means that significant percentage of documents in archival collections (sometimes as much as 30-40 percent of collections) cannot be made available to users online. Dickson reports similar difficulties with copyright clearance for archival materials and also recommends that a new definition of due diligence for manuscript and archival collections be developed that will define reasonable effort in copyright search and make it easier and less expensive to make such material available online.…”
Section: Preservation In the Digital Age 31mentioning
confidence: 99%